The Effect of Dynamic Beam Deflection and Focus Shift on the Acoustic Field Distribution Inside the Ultrasonic Ring Array - STASZEWSKI, Wiktor; GUDRA, Tadeusz; OPIELIŃSKI, Krzysztof J. (Archives of Acoustics, 2019)
This paper presents the results of acoustic field distribution simulations for the 1024-element ultrasonic ring array intended for the diagnosis of female breast tissue with the use of ultrasound tomography. For the purpose of analysing data, all acoustic fields created by each elementary transducer were combined. The natural position of the focus inside the ultrasonic ring array was changed by altering activation time of individual transducers in sectors consisting of 32, 64, and 128 ultrasonic transducers. Manipulating the position of the focus inside the array will allow to concentrate the ultrasonic beam in a chosen location in the interior space of the ring array. The goal of this research is to receive the best possible quality of images of cross-sections of the female breast. The study also analysed the influence of the acoustic field distribution on the inclination of the beam. The results will enable to choose an optimal focus and an optimal number of activated transducers.